Understanding liver cancer : a tale of two diseases - Carr, Brian I. (Springer Healthcare Ltd., 2014)
Understanding Liver Cancer is a concise and up-to-date review, which discusses diagnosis, management, patient care, current and emerging therapies, and useful resources that clinicians can provide to their patients. Busy healthcare professionals who want a quick review of liver cancer as well as a summary of current therapies will benefit from this succinct text.